Chronic Venous Insufficiency: An Updated Review for Nursing - Alserhri, Laila Mohammed Hassan; Alshehri, Hanan Mohammed Hassan; Alshehri, Jawaher Mohammed Hassan; Asiri, Halimah Ahmed Mohammed; Asiri, Reem Ahmad Mohammad; Asiri, Amal Talea Abdullah; Alshehry, Aishah Hezam Rajeh; Asiry, Damsah Lbrhim Abud; Albargi, Agil Atef A; Alshehri, Khulud Ali Mohammed; Albarqi, Mohammed Abu Bakar; Alqahtani, Saeed Hadi Hamad; et al. (Journal of Ecohumanism, 2024)
Background: Chronic venous disease (CVD) is a prevalent condition characterized by structural and functional abnormalities of the venous system, primarily affecting the lower extremities. It manifests through symptoms such as leg heaviness, swelling, varicose veins, and venous ulcers, significantly impacting patients’ quality of life and imposing substantial economic burdens on healthcare systems. The pathophysiology involves venous hypertension, inflammation, and valve incompetence, with risk factors including age, obesity, pregnancy, and genetic predisposition. Aim: This review aims to provide an updated overview of CVD, focusing on its etiology, epidemiology, pathophysiology, clinical evaluation, and management strategies. It emphasizes the role of nursing interventions and the importance of an interprofessional approach to optimize patient outcomes. Methods: The review synthesizes current literature on CVD, including diagnostic criteria, treatment modalities, and nursing protocols. It highlights evidence-based practices such as compression therapy, wound care, lifestyle modifications, and minimally invasive procedures like sclerotherapy and endovenous ablation. The role of the CEAP classification and Venous Clinical Severity Score (VCSS) in guiding treatment decisions is also discussed. Results: CVD management requires a multidisciplinary approach, with compression therapy and lifestyle modifications forming the foundation of treatment. Minimally invasive procedures and surgical interventions are effective for advanced cases. Nursing interventions, including patient education, wound care, and pain management, play a critical role in improving outcomes. Early diagnosis and adherence to treatment plans are essential to prevent complications such as venous ulcers, deep vein thrombosis, and cellulitis. Conclusion: Effective management of CVD relies on a combination of conservative measures, advanced therapies, and patient education. An interprofessional team approach, including nurses, physicians, and specialists, is crucial for optimizing care and reducing the burden of this chronic condition.